Comparative Report on the Algal Diversity of Dickwella, Sri Lanka at the Start of South-West Monsoon in 2015 and 2017 - Pathirana, P.B.M.; Thilakaratna, W.S.; Bamunuarachchi, N.I. (University of Jaffna, 2018)
This research was carried out at Dickwella algal bed to investigate the percentage abundance of algae diversity at the start of South-West monsoon in June 2015 and 2017. Three line transects such as TR 1, TR 2 and TR 3 that were parallel to the shore were positioned along the algal bed. A quadrat (0.5 m × 0.5 m) was placed at forty five (n = 45) sampling locations at 0.5 m intervals along each transect and the algal species within the quadrat were identified and the abundance of each species was recorded. Altogether 17 algal species were recorded in 135 quadrat samples. Species identification was made in-situ, and later confirmed by standard algal identification keys. Shannon Wiener diversity index (H’) and Simpson’s diversity index (D’) with respect to each transect were calculated separately. In 2015, the H’ for TR 1, TR 2 and TR 3 were 2.0, 2.27 and 2.32, while 0.78, 0.86 and 0.87 were recorded respectively for D’. The H’ in 2017 for TR 1, TR2 and TR3 were 1.60, 1.63 and 1.04, while, 0.72, 0.71 and 0.43 were recorded for D’, respectively. Sargassum sp. contributed the highest species percentage (23% in 2015) and (55.21% in 2017), while, the lowest percentage (1.47%) was contributed by Chaetomorpha antennina in 2015 and Halimeda discoidea (0.01%) in 2017. It was evidenced that Sargassum sp. dominates the Dickwella algal bed by out-competing other algal species
Keywords: algae; Dickwella; diversity; Sargassum sp.; Sri Lanka